PERSEPSI SISWA KELAS XI IS TENTANG KETERAMPILAN MENGAJAR GURU GEOGRAFI SMAN 1 KOTO XI TARUSAN - vhadel kusuma wijaya; Rahmanelli Rahmanelli (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to describe and explain the perceptions of class XI students about teacher skills; (1) opening and closing lessons, (2) asking questions, (3) giving reinforcement, (4) managing classes, (5) variations (methods), (6) explaining material, and (7) guiding groups. This type of research is qualitative with data collection techniques by observation, interviews, and documentation. The research informants were 6 students who were determined using purposive sampling. Data analysis techniques with data reduction, data display, and data verification. The findings of the study showed: (1) the perceptions of class XI IS students at SMAN 1 Koto XI Tarusan in opening and closing lessons, students were happy with the way the teacher did, (2) students' questioning skills, if no students asked then the teacher continued the lesson, (3) teaching skills in providing reinforcement, the teacher providing reinforcement, (4) teaching skills in managing the class that the teacher does as well as possible, (5) skills in making variations, the teacher uses media in the form of printed books and Geography LKS, (6) teaching skills in explaining the lesson that the teacher explains the lesson orally and in writing, (7) teaching skills in guiding small group discussions the teacher has carried out the task well, the teacher focuses students on the discussion theme.